Optimization of the duration of an echogram resulting from computer simulation of the acoustic properties of a room - GOŁĘBIEWSKI, R.; HOJAN, E.; WOJTCZAK, M.; PĘKALA, P. (Archives of Acoustics, 1998)
The authors of this paper investigated the ways to decrease the time of calculating an echogram in the computer simulation of the distribution of the sound field in a room. The authors emphasize the existence of a limiting moment tst up to which the simulation must be completed. The remaining part of the echogram may be treated as a stochastic amplitude (temporal distribution). The authors related the moment tst to the reverberation time RT and the early decay time, EDT, of a room.